Brain-gut axis and psychiatric disorders: A perspective from bibliometric and visual analysis - Chen, Pan; Zhang, Ling; Feng, Yuan; Liu, Yu-Fei; Si, Tong Leong; Su, Zhaohui; Cheung, Teris; Ungvari, Gabor S.; Ng, Chee H.; Xiang, Yu-Tao (Frontiers in Immunology, 2022)
Background: The Brain-Gut Axis, a bidirectional signaling pathway that connects the intestinal and central nervous systems, plays an important role in in the development of psychiatric disorders. However, the overall research trends in this field are unclear. This study explored the patterns of research on the brain-gut axis and psychiatric disorders from a bibliometric perspective. Methods: Relevant data were retrieved from the Web of Science Core Collection, with search terms on psychiatric disorders and the brain-gut axis. R (version 4.2.0), VOSviewer (version 1.6.17), CiteSpace software, and the online bibliometric platform were used in the data analysis. Results: A total of 2,298 articles published between 1993 and 2022 were identified, showing an increasing trend over time. China (1,859; 20.70%) was the country that contributed the most publications. The journal Nutrients (95; 4.13%) published the most publications. Cryan JF (153; H-index=73) and University College Cork (559; 22.54%) were the most influential author and the most productive institution, respectively. The high-frequency keywords were clustered into six themes, including neurodegenerative diseases, stress-related diseases, immune, brain behavior, depression, and probiotic-related topics; of which, depression (880; 2019), anxiety (207; 2018) and autism (191; 2019) were the most studied psychiatric disorders during the past 5 years. “Depressive symptom” (2019-2020) and “probiotic treatment” (2019-2020) were the main areas addressed in recent years. Conclusion: Research on the brain-gut axis and psychiatric disorders has attracted increasing attention in the past decade, with most publications being from high-income level countries. This study provides a useful perspective on understanding the research trends, key hot topics, and research gaps in this expanding field.